Effect of credit cards on customers' spending behavior: a comparative analysis of Islamic and conventional credit cards - Idris, Umar Muhammed; Jan, Muhammad Tahir (2013)
Purpose – The main purpose of this paper is to understand the attitude of Malaysian credit card holders towards spending and settlement behavior. It also attempts to highlight the effect of Islamic credit cards on the spending behavior of customers in comparison to that of conventional credit cards. Design/methodology/ approach – Data were collected using a structured questionnaire, distributed among the holders of conventional and Islamic credit card holders. A total of 200 questionnaires were distributed among the respondents in Klang Valley of Malaysia. The data collected were analyzed using Statistical Package for Social Science (SPSS). First, descriptive analyses were conducted followed by reliability tests and factor analysis. Findings – The findings of this research revealed that there is no effect of religion on the usage of credit card whether Islamic or conventional. Further, it is also found that conventional credit cards outweigh Islamic credit cards. It might be due the fact that Islamic credit cards are new compared to conventional counterpart. Research limitations/ implications - Given that this research is quantitative, there is a need to embark on in-depth study (qualitative) to understand the effect of credit cards on customers’ spending behavior in much better way. Practical implications – The results of this study give clear indications that there is a great need for the Islamic banks to enhance their credit card marketing in terms of the benefits it offers to the customers, particularly, the consideration to avoid riba in the transactions. Originality/ value – This study is a novel attempt to test the impact of credit cards on spending behavior of customers along with the comparison of Islamic cards with conventional cards.